THE ROLE OF IMARAH MANAGEMENT IN MUSALA IN IMPROVING THE QUALITY OF RELIGIOUS EDUCATION THROUGH THE QURAN EDUCATION PARK - Ardiyansah; Khasanah, Aulia Kurnia; Widyaningrum, Faisa; Al Aziz, Fikri Amiruddin; Muktamam, Mambaul Fikri; Hag, Nashrulloh Dhiyaul; dwijayanti, ita (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2024)
The prayer room is a place of worship for Muslims, especiallyfor carrying out congregational prayers and functions as acenter for the development of Islamic education andpreaching. This research focuses on imarah management inmaking the Nurul Fatah Musala prosperous in DukuhSidorejo through the activities of the Ta'lim Council and theAl-Qur'an Education Park (TPQ). The research results showthat the emirate is running well thanks to regular activityplanning. The activities of the Ta'lim Council, which isspecifically for mothers, and TPQ, which targets children,play an important role in improving the quality of religiouseducation. Teaching includes learning to read the Koran,memorizing prayers, and the basics of religion, usingcommunicative methods and ongoing guidance. The obstaclesencountered included the large number of children andlimited time, but were overcome by the learning while playingmethod. This research recommends improving learningmethods as well as developing further research on imarahmanagement in other prayer rooms.